Self-concept clarity and Internet addiction disorder among junior high school students: A moderate mediation model - Wang, Yue; Tang, Weiyi; Cao, Lei; Li, Ying (Frontiers in Psychiatry, 2022)
Introduction: As the epidemic spreads, the problem of Internet addiction stand out and getting serious. The present study aimed to investigate Internet addiction among junior high school students during the spread of the COVID-19, and to explore the mediating role of cognitive failure between self-concept clarity and Internet addiction, and the moderating role of mindfulness. Methods: A sample of 1, 153 junior high school students in Henan province were surveyed anonymously with Self-concept Clarity Scale(SCCS), Cognitive Failure Questionnaire(CFQ), Mindfulness Attention Awareness Scale(MAAS) and Internet Addiction Test(IAT). Results: (1) Self-concept clarity was negatively correlated with Internet Addiction; (2) Self-concept clarity not only had a direct effect on internet addiction, but also indirectly affect internet addiction through cognitive failure; (3) Mindfulness moderates the relationship between self-concept clarity and Internet addiction, as well as the relationship between cognitive failure and Internet addiction. Compared with low levels of mindfulness, both the protective effect of self-concept clarity and the effect of cognitive failure on Internet addiction were stronger among junior high school students who were at high levels of mindfulness. Conclusion: This study constructs a moderated mediation model to explain the effect of self-concept clarity on Internet addiction. It is effective to alleviate internet addiction by improving self-concept clarity and mindfulness level of the junior school students.